2022
DOI: 10.1002/adem.202101308
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Tunable Ni–Cu Core–Shell Nanoparticles—Structure, Composition, and Catalytic Activity for the Reverse Water–Gas Shift Reaction

Abstract: A facile and efficient methodology is described for the solvothermal synthesis of size‐tunable, stable, and uniform NiCu core–shell nanoparticles (NPs) for application in catalysis. The diameter of the NPs is tuned in a range from 6 nm to 30 nm and to adjust the Ni:Cu ratio from 30:1 to 1:1. Furthermore, the influence of different reaction parameters on the final NPs is studied. The NPs are structurally characterized by a method combination of transmission electron microscopy, anomalous small‐angle X‐ray scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Considering the RWGS reaction at 500 °C as an example, the CuNi/Al 2 O 3 catalyst yielded 79.7% selectivity for CO, similar to the previously reported CuNi catalysts. [39][40][41][42] Notably, with a similar CO 2 conversion, 93.5% selectivity for CO was obtained by DL2-RD20 at 500 °C. A more efficient mass transfer for the DL2-RD20 catalysts could promote the desorption of CO from the catalyst surface, improving CO selectivity.…”
Section: Catalytic Performancementioning
confidence: 62%
“…Considering the RWGS reaction at 500 °C as an example, the CuNi/Al 2 O 3 catalyst yielded 79.7% selectivity for CO, similar to the previously reported CuNi catalysts. [39][40][41][42] Notably, with a similar CO 2 conversion, 93.5% selectivity for CO was obtained by DL2-RD20 at 500 °C. A more efficient mass transfer for the DL2-RD20 catalysts could promote the desorption of CO from the catalyst surface, improving CO selectivity.…”
Section: Catalytic Performancementioning
confidence: 62%
“…For example, Heilmann et al . described the synthesis NiCu core‐shell NPs (see Figure 6a) for the reverse water‐gas shift reaction [48] . From SAXS patterns analysis, shown in Figure 6b, they concluded that NPs diameter was 6.8 nm with a distribution of 14 % using a Weibull distribution.…”
Section: Discussion Of Recent Literaturementioning
confidence: 99%
“… (a) TEM images of spherical 16 nm diameter NiCu nanoparticles and (b) SAXS curve of the same particles (black circles) and the fitted curve using a core‐shell‐shell model (red line). Adapted, with permission, from reference [48] . (c) TEM image of hollow porous AuPt nanostructures (top), scanning TEM images and elemental mapping images of distribution of Pt (red) and Au (green) in those nanostructures (middle and bottom) and (d) SAXS curves of hollow Au nanoshells (red line), hollow porous AuPt nanoshells (black line) and Pt NPs (green line), respectively; and their respective SAXS patterns (insets from left to right).…”
Section: Discussion Of Recent Literaturementioning
confidence: 99%
See 2 more Smart Citations